Safety and Effectiveness of Momordica Charantia on Glycemic Control in Prediabetes: A Literature Review - Putu Ngurah Pradnya Wibawa; Ni Putu Lia Juliantini (Publikasi Indonesia, 2026)
Prediabetes is a metabolic condition characterized by elevated blood glucose levels that do not yet meet the diagnostic criteria for type 2 diabetes mellitus but significantly increase the risk of developing diabetes and cardiovascular disease. Early intervention is essential to delay disease progression, and herbal medicine has gained attention as a potential alternative therapy due to its accessibility and perceived safety. One promising herbal agent is Momordica charantia (bitter melon), which contains bioactive compounds such as charantin, polypeptide-p, and vicine that may improve glycemic control by enhancing insulin sensitivity, increasing peripheral glucose uptake, and reducing hepatic glucose production. This study aimed to systematically evaluate the effectiveness of Momordica charantia in improving glycemic parameters and insulin resistance among individuals with prediabetes. This literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was conducted across PubMed, ScienceDirect, and OpenAlex databases for studies published between 2016 and 2026. The search strategy included keywords related to insulin resistance, prediabetes, type 2 diabetes mellitus, and Momordica charantia. Eligible studies included randomized controlled trials, clinical trials, and systematic reviews focusing on glycemic outcomes. Study selection, data extraction, and synthesis were performed based on predefined inclusion and exclusion criteria. The findings indicated that Momordica charantia may be a safe and potentially effective herbal intervention for glycemic management in individuals with prediabetes and type 2 diabetes mellitus. Regular consumption in powder or extract forms has been associated with reductions in fasting plasma glucose (FPG), improvements in insulin sensitivity as measured by the homeostatic model assessment of insulin resistance (HOMA-IR), and regulation of glucagon levels, supporting its potential role in metabolic control.